2023
DOI: 10.30872/jlpf.v4i1.2018
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Profil Kesalahan Siswa dalam Menyelesaikan Soal Keterampilan Berpikir Kritis Menggunakan Newman’s Error Analysis

Abstract: Penelitian ini bertujuan untuk mengidentifikasi profil kesalahan siswa dalam menjawab soal keterampilan berpikir kritis fisika menggunakan newman’s error analysis. Penelitian ini adalah penelitian deskriptif kualitatif yang didukung oleh data kuantitatif. Sampel penelitian ini adalah 16 siswa kelas XI IPA di MAN 4 Balangan. Teknik pengambilan sampel adalah sampling jenuh (sampel populasi). Pengumpulan data dalam penelitian ini menggunakan teknik tes, dan wawancara. Jenis kesalahan yang siswa lakukan dalam meng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…These results indicated that students split the complex data to be more manageable and understandable, under Angeli et al ( 2016 Then, the essential support indicator gained a percentage of 85%; this indicated that students determined the formula correctly from the questions given. The primary support indicator is students' basic skills in adjusting information from sources, observing, and considering the results (Magdalena & Muslim, 2023). Furthermore, the advanced clarification indicator had reached a percentage of 76%.…”
Section: Picture 2 Results Of Student Answersmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that students split the complex data to be more manageable and understandable, under Angeli et al ( 2016 Then, the essential support indicator gained a percentage of 85%; this indicated that students determined the formula correctly from the questions given. The primary support indicator is students' basic skills in adjusting information from sources, observing, and considering the results (Magdalena & Muslim, 2023). Furthermore, the advanced clarification indicator had reached a percentage of 76%.…”
Section: Picture 2 Results Of Student Answersmentioning
confidence: 99%
“…Moreover, according to Ennis in Magdalena and Muslim (2023), strategy and tactics indicators are students' skills in deducing and inducing information to make decisions from the results considered. Strategy and tactics indicators had the lowest percentage of 38%.…”
Section: Picture 2 Results Of Student Answersmentioning
confidence: 99%